Implementation of Fundraising Management at BAZNAS Hulu Sungai Tengah in Increasing ZIS Collection - Rama , Rama; Rofi'i, Rofi'i; Zulkifli, Zulkifli; Aviva, Itsla Yunisva (Universitas Al-Qolam Malang, 2025)
Indonesia has significant zakat potential, yet actual collection remains far below expectations. In Hulu Sungai Tengah (HST) Regency, for example, zakat potential is estimated at IDR 3.1 trillion, while BAZNAS HST collected only IDR 3.09 billion in 2024. This study aims to analyze the implementation of fundraising management at BAZNAS HST using the POAC (Planning, Organizing, Actuating, Controlling) framework, identify the fundraising strategies applied, and evaluate their impact on zakat, infaq, and sadaqah (ZIS) collection. A descriptive qualitative method was employed, with data collected through in-depth interviews with BAZNAS HST officials, direct observations, and financial report documentation, and analyzed using Miles and Huberman’s interactive model. The findings show that BAZNAS HST applied structured planning (RKAT), organizing through decreed teams, innovative programs such as Blessed Friday and Baznas Corner, and routine evaluations, which together increased ZIS collection from IDR 790.98 million in 2022 to IDR 3.09 billion in 2024, with muzakki rising from 134 to 207. Nevertheless, this improvement was also influenced by external factors, including post-pandemic religious awareness, digital zakat trends, inflation, and government support. The study contributes theoretically by affirming both the relevance and limitations of POAC in zakat management, and practically by offering a replicable fundraising model adaptable to local contexts.